Analisis Kepuasan Pelanggan PDAM Tirta Umbu Kabupaten Nias - Cardinal Pranatal Mendrofa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
PDAM Tirta Umbu, Nias Regency in providing services to the management and distribution of clean water has also not satisfied customers. There were 447 complaints or customer complaints during 2018. The purpose of this study is to find out and analyze the influence of service quality and want to know and analyze the most dominant service quality elements affecting customer satisfaction PDAM Tirta Umbu, Nias Regency. This research method is descriptive with survey method approach. The population numbered 9374 customers in 2018. Data collection techniques consisted of questionnaires and documentation studies. The sample technique is accidental, with statistical analysis of multiple regression analysis. The results of research and discussion, amounting to 51.3% of customer satisfaction PDAM Tirta Umbu is influenced by the five service quality variables, while the remaining 48.7% is influenced by other variables.